2020
DOI: 10.1111/1744-7941.12259
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing employee perceptions of human resource management: a review of China‐based literature and future directions

Abstract: Employee perceptions of human resource management (HRM) have attracted increasing attention in recent years. This review study aimed to examine the extent to which employee perceptions of HRM have been contextualized in China. We conducted a systematic literature search and review of 25 China-based empirical studies published in peer-reviewed academic journals in English. The review demonstrates that extant research mainly focuses on three distinct but inter-related dimensions: perceived HRM content, HRM syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 83 publications
2
30
0
Order By: Relevance
“…This study investigates how a Western-developed management tool influences China-specific employee behavior in an organizational culture with Chinese characteristics. Firstly, a strategic HRM view was widely accepted in Chinese firms, which has led to the use of high-performance work practices or systems ( Kim et al, 2012 ; Xiao and Cooke, 2020 ). High-performance work practices or systems have been reported as impacting on a series of work outcomes ( Kim et al, 2012 ), including OCB ( Sun et al, 2007 ; Shen and Benson, 2014 ; Zhang et al, 2014 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This study investigates how a Western-developed management tool influences China-specific employee behavior in an organizational culture with Chinese characteristics. Firstly, a strategic HRM view was widely accepted in Chinese firms, which has led to the use of high-performance work practices or systems ( Kim et al, 2012 ; Xiao and Cooke, 2020 ). High-performance work practices or systems have been reported as impacting on a series of work outcomes ( Kim et al, 2012 ), including OCB ( Sun et al, 2007 ; Shen and Benson, 2014 ; Zhang et al, 2014 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In today's competitive business environment, a greater emphasis is being placed on HRM practices to motivate employees to make extra-role contributions to the organization (Alfes et al , 2013; Xiao and Cooke, 2020). Our findings demonstrate that employees are more likely to perform OCB for the benefit of the organization when they have positive perceptions of HRM practices.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Thus, HRM practices play a central role in motivating employees to engage in OCB from the social exchange perspective ( (Blau, 1964;Lam et al, 2009;Meijerink et al, 2021;Newman et al, 2016). There is some empirical evidence that employees' perceived HRM practices relate positively to OCB in the Chinese context (Sun et al, 2007;Tang and Tang, 2012;Xiao and Cooke, 2020). Following theoretical reasoning and empirical findings, it is hypothesized that Chinese employees with a positive perception of HRM practices are more likely to exhibit OCB.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cooke and colleagues conducted several review studies on HRM in China that identified and suggested many contextual factors at different levels (Cooke, Xiao and Xiao 2021; Xiao and Cooke 2020). For instance, in a review article on SHRM in China (Cooke, Xiao and Chen 2020), they investigated contextual factors related to the strategic choices of HRM systems.…”
Section: Contextual Changes and The Re‐conceptualisation Of Chinese Tmmentioning
confidence: 99%
“…At the employee level, there were HR‐related factors that covered employee groups, managerial values, HR strategic roles, employee representation and workforce diversity. Xiao and Cooke (2020) explored potential contextual factors that might affect employee perceptions of HRM in the Chinese context, including institutional factors (Confucian culture, legislation systems, business environment, political context and historical trends), organisational factors (organisational strategies, implemented HR practice and organisational climate), interpersonal factors (leader‐member exchanges, leadership styles and interaction between colleagues) and individual factors (personal goals, cognitive schema, past experiences and demographic factors).…”
Section: Contextual Changes and The Re‐conceptualisation Of Chinese Tmmentioning
confidence: 99%